Sodium Channel and Sodium Pump in Normal and Pathological Muscles from Patients with Myotonic Muscular Dystrophy and Lower Motor Neuron Impairment - Desnuelle, C. (1982)
Two sodium transport systems have been analyzed in this work: the voltage-sensitive sodium channel and the (Na(+), K(+)) ATPase pump. The sodium channel has been studied using a tritiated derivative of tetrodotoxin; the sodium pump has been studied using tritiated ouabain. Properties of interaction of tritiated tetrodotoxin and of tritiated ouabain with their respective receptors were observed in normal human skeletal muscle and in muscles of patients with myotonic muscular dystrophy and with lower motor neuron impairment. Levels of sodium pump and of sodium channels were measured at different stages of membrane purification. Microsomal fractions of normal human muscle have maximal binding capacities for tetrodotoxin of 230 fmol/mg of protein and of 7.4 pmol/mg of protein for ouabain. Dissociation constant for the complexes formed by the tetrodotoxin derivative and by ouabain with their respective receptors were 0.52 nM and 0.55 μM, respectively. In muscles from patients with myotonic muscular dystrophy, the maximal binding capacity for tetrodotoxin, i.e., the number of Na(+) channels was found to be very similar to that found for normal muscle. The maximal binding capacity for ouabain, i.e., the number of Na(+) pumps was three- to sixfold lower than in normal muscle. Dissociation constants for the complexes formed with the tetrodotoxin derivative and with ouabain were the same as for normal muscle. In muscles from patients with lower motor nerve impairment, the maximal binding capacities for tetrodotoxin and for ouabain were twice as high as in normal muscle. Again, dissociation constants for the complexes formed with the tetrodotoxin derivative and with ouabain were nearly unchanged as compared with normal muscle. These results suggest that sodium transport systems involved in the generation of action potentials and/or in the regulation of the resting potential are altered both in myotonic muscular dystrophy and in lower motor neuron impairment.